BlockingαVβ3 Integrin Ligand Occupancy Inhibits the Progression of Albuminuria in Diabetic Rats - Laura A. Maile; Katherine Gollahon; Christine Wai; Paul Dunbar; Walker Busby; David Clemmons (Journal of Diabetes Research)
This study determined if blocking ligand occupancy of the αVβ3 integrin could inhibit the pathophysiologic changes that occur in the early stages of diabetic nephropathy (DN). Diabetic rats were treated with either vehicle or a monoclonal antibody that binds the β3 subunit of the αVβ3 integrin. After 4 weeks of diabetes the urinary albumin to creatinine ratio (UACR) increased in both diabetic animals that subsequently received vehicle and in the animals that subsequently received the anti-β3 antibody compared with control nondiabetic rats. After 8 weeks of treatment the UACR continued to rise in the vehicle-treated rats; however it returned to levels comparable to control nondiabetic rats in rats treated with the anti-β3 antibody. Treatment with the antibody prevented the increase of several profibrotic proteins that have been implicated in the development of DN. Diabetes was associated with an increase in phosphorylation of the β3 subunit in kidney homogenates from diabetic animals, but this was prevented by the antibody treatment. This study demonstrates that, when administered after establishment of early pathophysiologic changes in renal function, the anti-β3 antibody reversed the effects of diabetes normalizing albuminuria and profibrotic proteins in the kidney to the levels observed in nondiabetic control animals.